Assessing the impact of public perception and willingness-to-pay on reducing smog in Pakistan: Evidence from Lahore City - Riaz Ahmad; Fanglin Li; Ibrar Hussain; Azmat Hayat (Heliyon)
Smog pollution is a major global issue affecting Pakistan's major cities, particularly Lahore. The study aims to explore the public perception and willingness to pay (WTP) for smog reduction via the Contingent Valuation Method (CVM). This study uses a structured interview schedule and interval regression model to analyse the public perception and willingness to pay for smog reduction. Findings reveal that only 46 % of respondents perceive smog pollution “strongly severe,'' attributing it primarily to industrial (43 %) and vehicular (35 %) emissions. Furthermore, after receiving the information, the respondents' WTP increased from 68 PKR to 84 PKR. However, respondents were more willing to pay for self-protection than to support the control and preventive measures. Socioeconomic factors such as education and income significantly influence WTP for smog reduction. This research underscores the need for enhanced public awareness and participation in smog mitigation for sustainable development.